Touch me if you can: The intangible but grounded nature of abstract concepts. (19th June 2020) - Borghi, Anna M.; Tummolini, Luca
Abstract: Thinking about what the senses cannot grasp is one of the hallmarks of human cognition. We argue that "intangible abstracta" are represented differently from other products of abstraction, that goal-derived categorization supports their learning, and that they are grounded also in internalized linguistic and social interaction. We conclude by suggesting different ways in which abstractness contributes to cement group cohesion.